Caracterização e aplicação de zeólitas naturais - Soares, Fernanda Santiago Chaves (2010)
Zeolites are aluminosilicates with a three dimensional framework structure bearing AlO4 and SiO4 tetrahedra. These are linked to each other by sharing all of the oxygen to form interconnected cages and channels containing mobile water molecules and exchangeable cations. In this work, samples of natural zeolites, originating from mines in different countries, were characterized by physical and chemical methods and then evaluated as an adsorbent material for contaminants commonly found in industrial effluents. The micro devices construction was based on LTCC technology with zeolite inside and using the zeolite as a natural fertilizer support in a fertirrigation experiment employing vinasse in alfafa culture. The characterization experiments showed that the samples Zeolite 1 and Zeolite 2 consist in zeolites of the chinoptilolite type and the composition that the Zeolite 3 in maiming predominated by stilbite zeolite. Adsorption studies indicated the ability of the use of zeolites to metallic ions metal Cd(II), Co(II), Cr(III), Cu(II), K(I), Ni(II), Pb(II) and Zn(II) remotion from aqueous solutions and the possibility to remove of PO4 3- anion pre-concentration. The three evaluated zeolites showed capacity to remove Cr(III) and Pb(II) higher then other studied analytes. Time and pH were evaluated owing their interference in the ions adsorption ability. Miniaturized natural zeolite device inside the LTCC was construed and applied to aqueous ions adsorption presented be versatile in different system s detection. In the fertirrigation experiment was possible to detect the positive influence of the zeolite to increase the alfafa productivity.